THE ISSUE OF PROCEDURAL PASSIVE QUALITY IN THE PROCESSES WHICH CONCERN USUCAPTION - Diana Andreea TOMA (Challenges of the Knowledge Society)
In the Romanian legal system, usucaption is an original way of acquiring property rights. In court actions for the establishment of the existence of the right of ownership by virtue of usucaption, the question of the passive procedural quality has frequently been raised. The general rule is that the defendant is represented by the titleholder of the property to be usucaptioned. However, in practice there are different situations which need to be adapted to each individual situation. This paper aims to present the most common situations regarding the passive legal standing in actions for the establishment of ownership by virtue of usucaption.